UPAYA PENINGKATAN KETRAMPILAN DAN KREATIVITAS MELALUI KURSUS MENJAHIT DI PANTI ASUHAN RIYADLUL JANNAH DESA CIKERUH JATINANGOR - Herlina, Nina; Skober, Tanti Restiasih (Midang, 2026)
This community service project aims to enhance the creativity and independence of children at Riyadlul Jannah Orphanage, Cikeruh Village, Jatinangor Subdistrict, through sewing skills training. Conducted over two months, the program included preparation, implementation, and evaluation phases using a participatory and experiential learning approach. The participants consisted of 15 girls aged 10–17 years. The results show significant improvements in sewing techniques, creative thinking, and positive attitudes such as perseverance, responsibility, and cooperation. Beyond practical skills, the program strengthened participants’ self-confidence and independence. Socially, the activity fostered stronger relationships between the university, the orphanage, and the local community, and serves as a model for skill-based empowerment. This initiative contributes to the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education) and Goal 8 (Decent Work and Economic Growth).